2016
DOI: 10.1371/journal.pone.0166771
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Bt Cotton Does Not Disrupt the Top-Down Forces Regulating the Cotton Aphid in Central China

Abstract: Top-down force is referred to arthropod pest management delivered by the organisms from higher trophic levels. In the context of prevalent adoption of transgenic Bt crops that produce insecticidal Cry proteins derived from Bacillus thuringiensis (Bt), it still remains elusive whether the top-down forces are affected by the insect-resistant traits that introduced into the Bt crops. We explored how Bt cotton affect the strength of top-down forces via arthropod natural enemies in regulating a non-target pest spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…The lack of insecticide effects in short-term studies of arthropod communities has also been detected in other ecosystems, particularly tropical agroecosystems [ 72 , 84 ], where the cultivation system itself usually exhibits a more prominent effect and may buffer the potential insecticide impact [ 79 81 , 85 ]. While Bt proteins are constitutively expressed in the crop throughout the growing season, there is a lack of significant short- and long-term impacts on arthropod assemblages, as reported for maize [ 15 , 66 ], cotton [ 35 , 47 , 78 , 86 ] and soybean [ 87 ]. Yu et al [ 87 ] reported non-significant impact of Bt -soybean, but using general faunistic indexes rather than multivariate analyses with higher taxonomic resolution.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of insecticide effects in short-term studies of arthropod communities has also been detected in other ecosystems, particularly tropical agroecosystems [ 72 , 84 ], where the cultivation system itself usually exhibits a more prominent effect and may buffer the potential insecticide impact [ 79 81 , 85 ]. While Bt proteins are constitutively expressed in the crop throughout the growing season, there is a lack of significant short- and long-term impacts on arthropod assemblages, as reported for maize [ 15 , 66 ], cotton [ 35 , 47 , 78 , 86 ] and soybean [ 87 ]. Yu et al [ 87 ] reported non-significant impact of Bt -soybean, but using general faunistic indexes rather than multivariate analyses with higher taxonomic resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Han et al [ 48 ] assessed the current information related to the effects of insect-resistant GM crops on arthropod behavior and drew a conclusion that the majority of reports focused on behavior effects of target insects and the non-target herbivores were rarely affected. Longer egg duration and male adult longevity of the GRLHs on the testing RDV-infected Bt rice lines may slow their population growth, however, we noted that reduced population growth is not a general effect of GM crops [ 49 ]. Therefore, we conclude that growing Cry1C- and Cry2A-transgenic rice would pose a negligible risk to the GRLHs.…”
Section: Discussionmentioning
confidence: 99%
“…gossypii parasitoid communities in the cotton agroecosystems of northern China, reporting a total of three primary parasitoid species and 12 hyperparasitoids. Parasitoids are important natural enemies of cotton aphids in northern China 14 , 33 , with Lysiphlebia japonica widely assumed to be the dominant parasitoid species 18 , 21 , 23 – 29 . This parasitic wasp has been broadly studied in China, and applied research has quantified its impact on aphid population dynamics 33 , 34 , its oviposition behaviour and preferences in terms of host instar 35 and host plants 36 , and the effect of environmental conditions on its biological control efficacy 37 .…”
Section: Discussionmentioning
confidence: 99%
“…gossypii , parasitism rates tend to remain below 30% 17 – 21 . The dynamics of parasitoid wasp populations were only presented with the abundance of aphid mummies 22 , 23 , mummification rates 20 or Aphididae and hyperparasitoid proportions 18 . Cotton aphid parasitoids mainly belong to Aphidiinae (Braconidae) and Aphelinidae, with the former subfamily including Aphidius , Binodoxys , Lipolexis , Lysiphlebia , Lysiphlebus and Trioxys species.…”
Section: Introductionmentioning
confidence: 99%